11 Mortality Rates for Patients Admitted to Complex Care/Care of the Elderly Wards At Southmead Hospital, Bristol. (6th February 2020) - Burrell, A; Woodcraft, H; Devine, M
Abstract: Background: Existing data examining mortality rates following inpatient hospital admissions in the United Kingdom is either condition specific or examining all inpatient mortality based on single time point audits. This clinical effectiveness project aimed to assess 1, 3, 6 and 12 month mortality rates in patients admitted to complex care/care of the elderly (CC/CotE) wards at Southmead hospital, Bristol Methods: Data were collected by the trust's Business Insider department and analysed by the authors. All patients admitted to the four CC/CotE wards from July-December 2017 were included. Data collected included age, gender, date of admission, length of stay, date of discharge, and date of death if applicable. Results: 2673 patients were admitted to CC/CotE wards from July-December 2017. 42.72% of patients were male, mean age of patients was 82.46 years. Mean length of stay was 16.68 days, with mean length of stay on CC/CotE ward specifically 9.08 days. 292 (10.92%) of patients died during the index admission. Overall mortality rates were: 1 month: 11.34% (303 patients) 3 month: 21.59% (577 patients) 6 month: 30.15% (806 patients) 12 month: 38.53% (1030 patients) 12 month mortality increased with age from 75 upwards (34.04% in 75-79 years, 42.94% 85-89 years, 50.27% 95-99 years, 66.67% 100-104 years) but was similar in those aged 65-69 and 70-74 (29.41% and 28.18% respectively). Discussion: An improved understanding of mortality rates in patients admitted under CC/CotE may aid clinicians' ability to prognosticate. Appreciating that over a third of CC/CotE patients are potentially in the last year of life provides further impetus to begin advanced care planning discussions during inpatient admissions.